How “basic” is basic digital literacy for older adults? Insights from digital skills instructors - Vercruyssen, Anina; Schirmer, Werner; Geerts, Nelly; Mortelmans, Dimitri (Frontiers in Education, 2023)
With the continuing advancement of digitalization of everyday life, digital literacy becomes more and more a necessity. As a consequence, those who are digitally illiterate experience digital exclusion, which increasingly equals social exclusion. Older adults are typically less digitally active and also less skilled in digital technologies than younger cohorts. Hence, digital inclusion of older adults requires them to have proper access and skills to the digital world. Digital inclusion frameworks by governmental and supra-national organizations, on the one hand, and academic definitions of ‘digital literacy’ or ‘digital skills’, on the other hand, tend to include a broad set of competencies next to technical understanding, such as cognitive and social-emotional skills. However, in this article we address the problem that expectations of what digital literacy commonly entails are too high level for older adults with no pre-existing digital experience with computers, internet, smartphones, or tablets. Even what is considered as entry-level, basic digital skills, or foundational skills, can be very demanding for older adults with limited or no prior knowledge of and practice with digital technologies. To make our point, we draw on own data from interviews with 26 digital skills instructors who give training to older adults in Belgium (collected between December 2020 and February 2021). We provide empirical evidence for the circumstances that even seemingly basic digital skills, such as getting a device started or downloading apps, are very demanding and anything but trivial for older adults without prior experience. We demonstrate this along three interrelated domains: 1) ICT-jargon and terminology; 2) Hardware; 3) Software and Internet. Each of these domains entail hurdles of knowledge and understanding that need to be overcome for these older adults before we can start addressing the higher goals of digital literacy frameworks.